Temporal Accumulation and Decision Processes in the Duration Bisection Task Revealed by Contingent Negative Variation - Ng, Kwun Kei; Tobin, Simon; Penney, Trevor B. (Frontiers in Integrative Neuroscience, 2011)
The duration bisection paradigm is a classic task used to examine how humans and other animals perceive time. Typically, participants first learn short and long anchor durations and are subsequently asked to classify probe durations as closer to the short or long anchor duration. However, the specific representations of time and the decision rules applied in this task remain the subject of debate. For example, researchers have questioned whether participants actually use representations of the short and long anchor durations in the decision process rather than merely a response threshold that is derived from those anchor durations. Electroencephalographic (EEG) measures, like the Contingent Negative Variation (CNV), can provide information about the perceptual and cognitive processes that occur between the onset of the timing stimulus and the motor response. The CNV has been implicated as an electrophysiological marker of interval timing processes such as temporal accumulation, representation of the target duration, and the decision that the target duration has been attained. Hence, we used the CNV to investigate which durations are involved in the bisection categorization decision. The CNV increased in amplitude up to the value of the short anchor, remained at a constant level until about the geometric mean of the short and long anchors, when it began to resolve. These results suggest that the short anchor and the geometric mean of the short and long anchors are critical target durations used in the bisection categorization decision process. In addition, larger mean N1-P2 amplitude differences were associated with larger amplitude CNVs, which may reflect how precisely a participant is able to initiate timing on each trial across a test session. Overall, the results demonstrate the value of using scalp-recorded EEG to address basic questions about interval timing.